Development of Teach Pendent based Robotic Arm for Drawing using Mechatronics Approach - Harikrishnan Madhusudanan (IAES International Journal of Robotics and Automation (IJRA), 2016)
The main scope of this project is to use mechatronics approach to design and develop a complete humanoid robotic arm which can be used to draw different figures. A mechatronic approach is basically a synergistic combination of mechanical, electrical and control systems such that each and every stage of the product life cycle of the final product gets optimised. So, this approach which is used in this project would ensure that the robotic arm which would be the final product would have its design metrics optimised at each and every stage of its development cycle. The motive of developing this arm is to ensure that the final arm which is produced could be easily attached to the complete humanoid robot and would enable it to draw any kind of complex figures using highly accurate teach pendent mechanism.